Bicyclic‐Guanidine‐Catalyzed Asymmetric Michael Addition of 3‐Substituted Oxindoles to 2‐Cyclopentenone. Issue 12 (20th September 2013) - Yang, Caiyun; Chen, Wenchao; Yang, Wenguo; Zhu, Bo; Yan, Lin; Tan, Choon‐Hong; Jiang, Zhiyong
<x xml:space="preserve">Abstract</x> Taking the Michael: The first highly enantio‐ and diastereoselective Michael addition of various 3‐benzyl‐substituted oxindoles to 2‐cyclopentenone has been developed. A variety of 3, 3‐disubstituted oxindoles as Michael adducts were obtained in 69–99 % yield with 73–98 % ee and 9:1 to >20:1 d.r.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>